WAYS TO IMPROVE ANTERIOR ABDOMINAL WALL PLASTY FOR ABDOMINAL HERNIA AND ABDOMINOPOTOSIS - Khaydarova L.O. (Scholar Express Journals, 2023)
The results of examination and treatment of 121 operated patients with ventral hernia and abdominopotosis are presented. In patients with ventral hernia and abdominoptosis the adequate preoperative preparation and the use of the recommended algorithm of hernioallo- and alloplasty method selection allowed to reduce the frequency of postoperative complications from 14,8% to 8,9% (p=0,045), as well as wound complications from 11,5% to 4,5%.
Keywords: Ventral hernia; abdominoptosis; surgical treatment